Improvement of LV Reverse Remodeling Using Dynamic Programming of Fusion-Optimized Atrioventricular Intervals in Cardiac Resynchronization Therapy - Wang, Zhongkai; Li, Pan; Zhang, Bili; Huang, Jingjuan; Chen, Shaoping; Cai, Zhuhong; Qin, Yingyi; Fan, Jihai; Tang, Wendong; Qin, Yongwen; Li, Ruogu; Zhao, Xianxian (Frontiers in Cardiovascular Medicine, 2021)
Background: The patient-tailored SyncAV algorithm shortens the QRS duration (QRSd) beyond what conventional biventricular (BiV) pacing can. However, evidence of the ability of SyncAV to improve the cardiac resynchronization therapy (CRT) response is lacking. The aim of this study was to evaluate the impact of CRT enhanced by SyncAV on echocardiographic and clinical responses. Methods and Results: Consecutive heart failure (HF) patients from three centers treated with a quadripolar CRT system (Abbott) were enrolled. The total of 122 patients were divided into BiV+SyncAV (n =68) and BiV groups (n =54) according to whether they underwent CRT with or without SyncAV. Electrocardiographic, echocardiographic, and clinical data were assessed at baseline and during follow-up. Echocardiographic response to CRT was defined as a ≥15% decrease in left ventricular end-systolic volume (LVESV), and clinical response was defined as a NYHA class reduction of ≥1. At the 6-month follow-up, the baseline QRSd and LVESV decreased more significantly in the BiV+SyncAV than the BiV group (QRSd -36.25±16.33 ms vs. -22.72±18.75 ms, P <0.001; LVESV -54.19±38.87 ml vs. -25.37±36.48 ml, P <0.001). Compared to the BiV group, more patients in the BiV+SyncAV group were classified as echocardiographic (82.35% vs. 64.81%; P =0.036) and clinical responders (83.82% vs. 66.67%; P =0.033). During follow-up, no deaths due to HF deterioration or severe procedure related complications occurred. Conclusion: Compared to BiV pacing, BiV combined with SyncAV leads to a more significant reduction in QRSd and improves LV remodeling and long-term outcomes in HF patients treated with CRT.